Bone-Protective Effects of Dried Plum in Postmenopausal Women: Efficacy and Possible Mechanisms - Arjmandi, Bahram H. (Nutrients, 2017)
Osteoporosis is an age-related chronic disease characterized by a loss of bone mass and quality, and is associated with an increased risk of fragility fractures. Postmenopausal women are at the greatest risk of developing osteoporosis due to the cessation in ovarian hormone production, which causes accelerated bone loss. As the demographic shifts to a more aged population, a growing number of postmenopausal women will be afflicted with osteoporosis. Certain lifestyle factors, including nutrition and exercise, are known to reduce the risk of developing osteoporosis and therefore play an important role in bone health. In terms of nutrition, accumulating evidence suggests that dried plum (Prunus domestica L.) is potentially an efficacious intervention for preventing and reversing bone mass and structural loss in an ovariectomized rat model of osteoporosis, as well as in osteopenic postmenopausal women. Here, we provide evidence supporting the efficacy of dried plum in preventing and reversing bone loss associated with ovarian hormone deficiency in rodent models and in humans. We end with the results of a recent follow-up study demonstrating that postmenopausal women who previously consumed 100 g dried plum per day during our one-year clinical trial conducted five years earlier retained bone mineral density to a greater extent than those receiving a comparative control. Additionally, we highlight the possible mechanisms of action by which bioactive compounds in dried plum exert bone-protective effects. Overall, the findings of our studies and others strongly suggest that dried plum in its whole form is a promising and efficacious functional food therapy for preventing bone loss in postmenopausal women, with the potential for long-lasting bone-protective effects.